Artistic relations (Yale Univ. Press, 1994)
Structures of cultural production in nineteenth-century France / Michael Moriarty – The link between literary and artistic struggles / Pierre Bourdieu – 'A tout prix devenir quelqu'un' : the women of the Acad(c)♭mie Julian / Germaine Greer – Writing the arts : aesthetics, art criticism and literary practice / David Scott – The problem with colour. Three theorists : Goethe, Schopenhauer, Chevreul / Bernard Howells – Book illustration / S(c)♭gol(c)·ne Le Men – 'Telle main veut tel pied': Balzac, Ingres and the art of portraiture / Michael Tilby – The model's unwashed feet : French photography in the 1850s / Eric Homberger – Manet's textual frames / Robert Lethbridge – Newspaper and myth : migrations of the romantic image / Peter Collier – Transpositions / David Kelley — Stendhal's art history and the making of a novelist / Ann Jefferson – Victor Hugo, somnambulist of the sea / Roger Cardinal – Avatars of the artist : narrative approaches to the work of the painter / Patrick O'Donovan – The writing on the wall : descriptions of painting in the art criticism of the French Symbolists / James Kearns – Rimbaud : the shaping of a vision / Roger Little – Sex and the occult in Symbolist art and literature / Timothy Mathews – Val(c)♭ry and Rodin : Orpheus returning / Peter Collier – Dancing with Mallarm(c)♭ and Seurat (and Loie Fuller, H(c)♭rodiade and La Goulue) / Mary Ann Caws
Includes bibliographical references (p. 303-337) and index
Keywords: Aufsatzsammlung; Art and literature; Arts; French; Ut pictura poesis (Aesthetics)